DAMPAK AKUISISI PT AGUNG PODOMORO LAND, TBK TERHADAP REAKSI PASAR SEKTOR PROPERTI BURSA EFEK INDONESIA - Andriani, Ayu Dessy; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2016)
The aim of this study is to test the reaction of the capital market in the property sector in the Indonesia Stock Exchange on the acquisition announcement of PT Agung Podomoro Land, Tbk. This study used 10 sample of  property companies in the Indonesia Stock Exchange. This study used  t test and paired sample t-test as data analysis technique.The market's reaction occurs in H-5, H-2, H+4, H+5 evidenced by an average abnormal return statistically significant. It shows that the acquisition announcement of PT Agung Podomoro Land Tbk contains information. While on H-4, H-3, H-1, H0, H+2 H+2 and H+3 was not statistically significant. The results of paired sample t-test shows that there was no significant difference before and after the acquisition announcement of PT Agung Podomoro Land, Tbk.
Keywords: Acquisitions, Market Reaction, Abnormal Return, Event Study